Natural disaster and political trust: A natural experiment study of the impact of the Wenchuan earthquake. (January 2020) - You, Yu; Huang, Yifan; Zhuang, Yuyi
How do natural disasters impact political trust in contemporary China and what is the causal mechanism? Existing literature indicates that the severity of disaster, government relief effort and information dissemination are three key factors influencing people's political trust in the context of acute natural disasters. This study uses the Wenchuan earthquake as a natural experiment and focuses specifically on the survey data collected right before and after the earthquake. It finds that primarily due to the 'rally round the flag' effect and extensive media coverage, public trust in government officials at all levels rose significantly after the earthquake. During the crisis, state-run media played a vital intermediate role. The more a citizen was exposed to the official media coverage, the more likely his/her political trust was to increase. However, the division of work in disaster relief among different levels of government resulted in differences in the level of increase in trust. As local-level governments are often directly responsible for the rescue and post-earthquake relief, they gained the highest increase in political trust, while state-level officials gained the least. The short-run upsurge in political trust receded as time went by. Government mobilization and media coverage are core contributing factors to the increase in political trust during the post-disaster period. Nevertheless, the key to consolidating political legitimacy lies in long-term efforts to build good and effective governance.